2014
DOI: 10.1002/pon.3521
|View full text |Cite
|
Sign up to set email alerts
|

Measuring psychosocial functioning in the radiation oncology clinic: a systematic review

Abstract: Psychosocial function declines in approximately one-third of RT patients. Anxiety can dissipate after initiation of RT, whereas depression can persist throughout and after RT. Severe physical symptoms and time-related factors most robustly predict psychosocial function decline, which can be improved by psychotherapy and interventions aimed to improve patient education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 90 publications
3
36
0
1
Order By: Relevance
“…Moreover, women and younger patients showed higher scores in clinical symptoms of anxiety, depression and emotional distress. These data support the Dunn et al's [33] results and Hess and Chen's review [5] with patients undergoing radiotherapy.…”
Section: Psychopathological Disorders Structured Interview Mini and supporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, women and younger patients showed higher scores in clinical symptoms of anxiety, depression and emotional distress. These data support the Dunn et al's [33] results and Hess and Chen's review [5] with patients undergoing radiotherapy.…”
Section: Psychopathological Disorders Structured Interview Mini and supporting
confidence: 90%
“…A significant decrease was observed in the levels of anxiety and emotional distress from the beginning of radiotherapy to the end of radiotherapy and the followup period, without significant differences being observed from the end of radiotherapy to the follow-up. The anxiety levels were similar to those reported in Hess and Chen's [5] or Stiegelis et al's [6] reviews. In Neilson et al's paper [10], an increase in the probable cases of clinical depression was found at the end of the treatment, followed by a decrease in the follow-up period, while the probable cases of anxiety decreased three weeks after the treatment, and then increased at the 18 months follow-up.…”
Section: Psychopathological Disorders Structured Interview Mini and supporting
confidence: 86%
See 3 more Smart Citations